Sequential augmentation reveals life history and suitable conditions for colonization of the rare mahogany mistletoe in South Florida. Issue 4 (11th January 2017) - Duquesnel, Janice A.; Maschinski, Joyce; McElderry, Robert; Gann, George D.; Bradley, Keith; Cowan, Ernest
Abstract: Successfully reintroducing rare plant populations to recover historical community composition may require multiple efforts and greater lengths of time than is typically devoted by researchers. To improve the probability of successful colonization and to learn about the life history of the regionally endangered mahogany mistletoe ( Phoradendron rubrum ) in the Florida Keys, United States, we conducted sequential augmentations for 10 years across two host tree sizes, two seed sources, and six recipient sites. Long‐term monitoring for 13 years revealed that sowing fresh seeds in dry periods from introduced versus wild plants onto small diameter trees (<20 cm diameter at breast height [dbh]) that had branch diameters 15–20 mm resulted in the greatest colonization success. An average of 38.7% of seeds germinated and 23.8% survived to 2015. Plant development was quite slow. Seeds required over 100 days to germinate, 1.6 years for cotyledon emergence, and over 4.7 years to produce fruit. We detected first recruitment nearly 8 years after installation. Population growth improved following multiple attempts and expanded spatial extent as is predicted by theory. Portions of the life cycle are undetectable and thus could give false indications of reintroduction success or failure. Achieving and documenting unequivocal success of this reintroduction has required over a decade.